Public policies of local development and social capital densification: analysis of the Food Acquisition Program (FPA) in four municipalities of Minas Gerais - Simão, Gustavo Leonardo; Freitas, Alan Ferreira de; Silva, Edson Arlindo; Bastos, Bianca Ribeiro de Nardi; Salgado, Rafael Junior dos Santos F.; Amodeo (in memoriam), Nora Beatriz Presno (Revista de Administração da UFSM, 2017)
The paper analyzed the effectiveness of the Food Acquisition Program (FPA) as a public policy of local development, in densify the level of social capital in four cities in the state of Minas Gerais. Data was collected by conducting semi-structured interviews with several segments of actor involved in the implementation and operation of the FPA, subsequently categorized and analyzed by operating categories of social capital previously defined. Results indicated that the analyzed regions have low levels of social capital. Moreover, the existence of operational biases in the design and implementation of the FPA, notably in relation to deficiency in government communication among all the actors involved and the limited function of collective organizations, favors the perpetuation of the status quo. Thus, the modern model of the government intervention, arising with implementation the FPA, not have been transformer in relation to local development, in the cities studied. This scenario, however, can be changed when there is support from the municipal government and the existence of local leaders among the beneficiaries.